Moving to market restructuring transport in the former Soviet Union - Strong, John S.; Meyer, John Robert 1927-2009 (Harvard Inst. for Internat. Development, 1996)
In 1992, the European Bank for Reconstruction and Development commissioned four studies of rail, road, air, and water transport in the republics of Russia, Ukraine, Belarus, and Kazakhstan. This book combines these studies in a comprehensive assessment of transport at the advent of transition from centrally-planned to market economics. Energy, trade, and environmental policies, in the context of central planning, resulted in the world's most transport-intensive economy. The transition economies represent a distinct type of transport environment, with adequate physical capacity but lacking in many dimensions of service and quality. This book assesses key policy issues, restructuring needs, and organizational changes facing each sector in the transition to a market-oriented transport system.
Keywords: Gemeinschaft Unabhängiger Staaten; Herstructurering; Vervoer; Vervoersbeleid; Wirtschaftspolitik; Transportation and state -- Former Soviet republics; Transportation -- Former Soviet republics; Transport; Verkehr; Former Soviet republics -- Economic policy